2015
DOI: 10.1016/j.bbamcr.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic and proangiogenic role of calcium sensing receptor is linked to secretion of multiple cytokines and growth factors in breast cancer MDA-MB-231 cells

Abstract: Breast cancer metastasis to the bone, potentially facilitated by chemotactic and angiogenic cytokines, contributes to a dramatic osteolytic effect associated with this invasive behavior. Based on the intrinsic ability of calcium sensing receptor (CaSR) to control hormonal secretion and considering its expression in the breast, we hypothesized that CaSR plays a chemotactic and proangiogenic role in highly invasive MDA-MB-231 breast cancer cells by promoting secretion of multiple cytokines. In this study, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 100 publications
0
30
1
Order By: Relevance
“…In a smaller study from Li et al (24), on a TMA of 148 primary breast tumors, protein expression of CaSR was reported to be down-regulated in neoplastic tissue compared with normal-appearing tissue, and lower CaSR expression was significantly associated with an increased risk of lethal breast cancer progression. The findings by Li et al contrast with our own findings and with prior experimental evidence that suggest CaSR signaling promotes metastatic growth of breast cancer to bone (1,22,25). However, in the context of colorectal cancer and parathyroid tumors, higher CaSR expression has been observed to be protective (26).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In a smaller study from Li et al (24), on a TMA of 148 primary breast tumors, protein expression of CaSR was reported to be down-regulated in neoplastic tissue compared with normal-appearing tissue, and lower CaSR expression was significantly associated with an increased risk of lethal breast cancer progression. The findings by Li et al contrast with our own findings and with prior experimental evidence that suggest CaSR signaling promotes metastatic growth of breast cancer to bone (1,22,25). However, in the context of colorectal cancer and parathyroid tumors, higher CaSR expression has been observed to be protective (26).…”
Section: Discussioncontrasting
confidence: 83%
“…These effects were not observed in the epithelial-derived LNCaP prostate tumor cells (4). Similarly, in bone metastasizing renal cell carcinoma and breast cancer cell lines, extracellular calcium treatment promoted the up-regulation of angiogenic growth factors (22) and the PI3K/AKT pathway and down-regulated PTEN (22,23). Yano et al (3) reported CaSR activation in PC-3 prostate tumor cells by extracellular calcium induced production of the PTH-related protein, which may in turn promote bone resorption and further calcium release, potentially creating a cycle that is favorable for inducing bony metastases (21).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Dissolution of HA coatings can enhance calcium concentrations in the culture medium [6], which, for example, may activate calcium sensing receptors regulating cytokine and growth factor production [59]. Coatings with elevated carbonate content released more calcium, consistent with the known increase in solubility of carbonated apatite as compared to HA (Suppl.…”
Section: Resultsmentioning
confidence: 89%
“…It has demonstrated pro-angiogenic properties in rats via its action on VEGF and Tie-249. GM-CSF has been detected in MDA-MB-231 conditioned media50 but is apparently absent from triple negative tumor samples in humans51. On the other hand, GM-CSF is considered an important mediator of angiogenesis and invasion in a wide variety of solid tumors52.…”
Section: Discussionmentioning
confidence: 99%